Nuclear hormone receptor functions in keratinocyte and melanocyte homeostasis, epidermal carcinogenesis and melanomagenesis - Hyter, Stephen (2013)
Skin homeostasis is maintained, in part, through regulation of gene expression orchestrated by type II nuclear hormone receptors in a cell and context specific manner. This group of transcriptional regulators is implicated in various cellular processes including epidermal proliferation, differentiation, permeability barrier formation, follicular cycling and inflammatory responses. Endogenous ligands for the receptors regulate actions during skin development and maintenance of tissue homeostasis. Type II nuclear receptor signaling is also important for cellular crosstalk between multiple cell types in the skin. Overall, these nuclear receptors are critical players in keratinocyte and melanocyte biology and present targets for cutaneous disease management.